Parasitos digenéticos, copépodo e acanthocephala de masturus lanceolatus (molidae) encalhados ao norte do sudoeste atlântico, brasil - Figueiredo, Naibe Cristina de (Universidade Federal Rural do Semi-Árido, 2018)
Fish of the family Molidae, order Tetraodontiformes, are distributed throughout all oceans. Molas are the largest teleosts on Earth. They can measure up to 1.8 m in horizontal length and up to 2.4 m in vertical length, The Molidae comprises 4 species: Mola mola (Linnaeus, 1758), Ranzania laevis (Pennant, 1776), Masturus lanceolatus (Liénard, 1840), and Mola ramsayi (Giglioli, 1883). These fish have the highest parasite burdens among aquatic vertebrates. Molas are appropriate intermediate, paratenic, and definitive hosts as they are capable of carrying a large diversity of parasites. This study aimed to investigate the parasitic fauna of Masturus lanceolatus (sharptail mola; common names in Brazil: “peixe-lua-rabudo”, “peixe-lua”; “mola”) (Molidae) stranded along the Brazilian coast, southwest Atlantic. Between 2009 and 2016, 5 specimens of M. lanceolatus (Molidae) stranded on beaches located in the States of Rio Grande do Norte (RN) and Ceará (CE), northeast Brazil. Fish necropsies and parasite sampling were carried out by researchers from the PCCB (rescue and rehabilitatiion programme “Projeto Cetáceos da Costa Branca”, RN/CE, Brazil). Fish capture, post-mortem examination, sample collection, and transportation of biological materials (ABIO) were authorized by the Brazilian Institute for the Environment and Renewable Natura; Resources (IBAMA) which issued a permit (n. 269/2013) for purposes of scientific research. Parasite specimens were fixed in 10% formalin and preserved in labeled vials containing 70% alcohol. Each sample received an accession number and was then submitted to the Laboratory of Studies in Immunology and Wildlife (LEIAS) and to the Laboratory of Aquatic Health (LASA) in Brazil for parasite identification to species level by light microscopy. A total of 197 parasite specimens were sampled from 5 necropsied molas (M. lanceolatus). These specimens were identified as Digenea, Crustacea, and Acanthocephala; 193 digenea trematodes, 3 crustaceans, and 1 acanthocephalan were recovered from these fish; the following species of parasites were found in the molas examined postmortem: 3 different species of Digenea: Accacladocoelium macrocotyle, Accacladocoelium nigroflavum, and Dihemistephanus lydiae; 1 species of Crustacea: Caligus bonito; and 1 species of Acanthocephala: Rhadinorhynchus pristis. The present study contributes to the existing body of knowledge on fish parasitology as 4 new species of internal parasites infesting M. lanceolatus are reported. To the authors’ knowledge, this is the first time that some of these species of endoparasites are described in the sharptail mola in Brazil
Keywords: Influência parasitária; Parasitismo; Peixe-lua-rabudo; Teleósteo; Parasitic influence; Parasitism; Sharptail mola; Peixe-lua-rabudo; Masturus lanceolatus; Teleost; Stranded fish; CIENCIAS AGRARIAS::ZOOTECNIA